MAIN DIRECTIONS OF OPTIMIZATION TAX SYSTEMS OF RK - Myrzakhanova D.Zh; Smagulova R.U; Taspenova G.A; Utegulova B.S (Academic Journal of Physical and Chemical Sciences, 2019)
The relevance of article is that the taxation system of RK operating today does not provide optimum performance of the functions, namely the sufficient level of taxation, for a covering of the main expenses of budgets and also does not promote normal functioning of economy of the state, economic growth and development of the enterprise environment. In such situation special importance is gained for the state and the enterprises by improvement, development new and realization of the existing ways of optimization of the taxation system. The purpose of article is identification and the analysis of the main directions of optimization of the taxation system of RK. Desire of the state and its subjects to optimize the taxation system became a natural stage of development of the tax relations in RK which began to be under construction with transition to market economy. High level of interest of the parties, lack of balance in tax legal relationship, a specific role of the enterprises in modern economy, the sequence of development of the domestic taxation system and some other smaller prerequisites caused high relevance of this direction for reforming.